Studi Karakteristik Marshall Pada Campuran Lapis Aspal Beton (Laston) dengan Bahan Tambah Limbah Kain Nilon - Yusnianti, Yusnianti; Sufrianto, Sufrianto; hujiyanto, hujiyanto; Syamsuddin, Syamsuddin (Universitas Sulawesi Tenggara, 2023)
The use of nylon fabric waste as adding material for concrete asphalt layers can be one of the solutions, because it can reduce pollution in the environment.The level of variation in adding nylon fabric waste is 0%, 5%, 10% and 15%. Sample testing as many as 24 test specimens. . The purpose of this study is to determine the physical properties of the asphalt with the added material of the nylon fabric waste and to determine the properties of the concrete asphalt layer mixture (Laston) with the added material of the nylon fabric waste. The results of testing the addition of nylon fabric waste levels as added material to the asphalt show that the value of the physical properties of asphalt is penetration, soft point, specific gravity, flame point and fuel point and asphalt dactality meets the standard specifications of the 2018 SNI Marga. As well as the addition of nylon substitution waste a number of asphalt at 5%, 10% and 15% content can affect the nature of concrete asphalt layers (Laston). In variations of 5%, 10% and 15% density value of 2,336 gr/cm, 2,327 gr/cm, 2,343 gr/cm, stability of 1892,4 kg, 2239,0 kg, 1953,6 kg, VMA of 15,9%, 16,2%, 15,6%, VIM of 4,4%, 4,7%, 4,1%, VFB of 73,6%, 70,9%, 74,0%, melting of 3,93 mm, 3,43 mm, 3,02 mm and MQ of 480,1 kg/mm, 652,9 kg/mm, 691,5 kg/mm.